2015
DOI: 10.14512/gaia.24.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Effects in Energy Efficiency — an Inefficient Debate?

Abstract: Reaction to Two Articles on Rebound Effects: T. Santarius. 2014. GAIA 23/2: 109‐117. B. Alcott. 2014. GAIA 23/4: 304‐305

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…When reflecting on their own daily life and expenses, people did not have an idea how they spend saved money: it mostly stays in their bank account and is spent 'at some point'. This lack of awareness fits current knowledge that individuals regularly are neither fully informed nor act fully rationally in the economic sense (e.g., Thaler, 1980;Friedrichsmeier and Matthies, 2015). Frederick et al (2009) for example showed that the assumption that consumers consider the opportunity costs of a purchase and therefore actively think about alternatives that this purchase would displace is incorrect.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…When reflecting on their own daily life and expenses, people did not have an idea how they spend saved money: it mostly stays in their bank account and is spent 'at some point'. This lack of awareness fits current knowledge that individuals regularly are neither fully informed nor act fully rationally in the economic sense (e.g., Thaler, 1980;Friedrichsmeier and Matthies, 2015). Frederick et al (2009) for example showed that the assumption that consumers consider the opportunity costs of a purchase and therefore actively think about alternatives that this purchase would displace is incorrect.…”
Section: Discussionsupporting
confidence: 61%
“…Negative spillover is often attributed to moral licensing (Galizzi and Whitmarsh, 2019;Maki et al, 2019). Additionally, moral licensing is used as a psychological explanation for the rebound effect (Friedrichsmeier and Matthies, 2015).…”
Section: Psychological Pathway: Moral Licensingmentioning
confidence: 99%
“…As Gardner and Stern [5] emphasize, it should not be the question of "either-or". Behavioral changes of both types are necessary to implement truly sustainable behavior, and daily behaviors can determine the net benefit of energy-relevant investments (e.g., the issue of rebound; see [76,77]). Nevertheless, it is also most important to reduce the imbalance between research on investment decisions and curtailment behaviors in order to reach behavioral changes in both areas.…”
Section: Final Remarksmentioning
confidence: 99%
“…3 The prevalence of those positive effects, however, is discussed controversially due to the potential occurrence of rebound effects, which suggest that increased EE ceteris paribus leads to energy price decreases and hence, via different links such as income or substitution effects, to an increased utilization of energy (e.g. Sorrell, 2007;Herring and Sorrell, 2008;Madlener and Alcott, 2009;Friedrichsmeier et al, 2015;Lutz and Breitschopf, 2016).…”
Section: Introductionmentioning
confidence: 99%